Outcomes of Integrating Total Station and Surfer8 Software in Survey Practice Laboratory - Muntasher, Khalida; Kittur, Javeed (Journal of Engineering Education Transformations, 2018)
At KLE Technological University, Surveying is a core 4 credit course for undergraduate civil engineering students, where a lecture-only mode of delivery is provided for 160 students in III semester. The curriculum was set to refine for up-to-date technology and to contribute for the enhancement of students acquiring industry-based skills. As a part of curriculum, the objective is to provide significant amount of hands-on training on Total Station and Surfer8 software to obtain adequate learning outcomes. This is achieved through laboratory courses like Survey Practice I in III semester and Survey Practice II in IV semester. In order to achieve these objectives, the students of semester IV were introduced with the equipment 'Total Station' which they used to carry out the open ended experiment in Survey Practice II laboratory course. This activity was implemented successfully for the first time in curriculum for the semester IV students. Total Station is a real-time system embedded with an onboard computer used for displaying and storing the data. The open ended experiment was divided into three tasks; traversing civil engineering department area, performing profile leveling using total station and mapping using the software Surfer8. This activity was scheduled for three weeks; data collection (first week), hands-on software training (second week) and report submission and assessment using rubrics (third week). The objectives of the activity were measured using three parameters. As per the assessment, the attainment of parameters data collection and documentation is 82.45% and 80.91%, whereas the attainment of the parameter analysis using software is comparatively less which is 75.67%.